The Political Economy of Food Price Policy in Zambia - Chapoto, Antony (Oxford University Press, 2015)
The global food price crisis of 2007–8 raised fears about the impacts of higher and more volatile food prices for the poor in Zambia. Like in the past, the implementation of the strategies to deal with the rising food prices, especially for the staple crop maize were delayed due to ineffective response policies, mistrust between government and private sector, protracted discussions, inaction amongst key agriculture stakeholders and rent-seeking behaviour by some. Using the political economy framework, this study examines how the country responded to the 2007/08 global food crisis and the lessons learnt for dealing with future food crises.